2020
DOI: 10.3390/ijms21249536
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Mutational and Phenotypic Characterization of New Metastatic Cutaneous Squamous Cell Carcinoma Cell Lines Reveal Novel Drug Susceptibilities

Abstract: Cutaneous squamous cell carcinoma (cSCC) is a common skin cancer. Most patients who develop metastases (2–5%) present with advanced disease that requires a combination of radical surgery and adjuvant radiation therapy. There are few effective therapies for refractory disease. In this study, we describe novel patient-derived cell lines from cSCC metastases of the head and neck (designated UW-CSCC1 and UW-CSCC2). The cell lines genotypically and phenotypically resembled the original patient tumor and were tumoro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(37 citation statements)
references
References 61 publications
2
35
0
Order By: Relevance
“…In general, the present study found that tumor-, subtype- and patient-specific features were conserved in the cell lines compared to their original tissue samples, while genes associated with immune response, cell adhesion and angiogenesis were downregulated. This is consistent with the results by Perry et al, who compared two human squamous cell carcinoma cell lines to their original tumor tissues [ 42 ]. Importantly, regarding the tumor entity, only few deviations were found between cell lines and tissues regarding the prostate and bladder cancer pathways.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…In general, the present study found that tumor-, subtype- and patient-specific features were conserved in the cell lines compared to their original tissue samples, while genes associated with immune response, cell adhesion and angiogenesis were downregulated. This is consistent with the results by Perry et al, who compared two human squamous cell carcinoma cell lines to their original tumor tissues [ 42 ]. Importantly, regarding the tumor entity, only few deviations were found between cell lines and tissues regarding the prostate and bladder cancer pathways.…”
Section: Discussionsupporting
confidence: 93%
“…The optimal reference for characterizing a cell line is the original tissue from which it was initially derived. However, in most cases, such a sample is either not available or not suitable for RNA-seq, and thus, such studies are scarce [ 42 ]. The sample set analyzed herein, consisting of canine cell lines derived from four PAC, two PAC metastases and three TCC and their original tumor tissues, provides a rare opportunity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Many commercial drug libraries are available to screen for targeted inhibitors that may impact survival of cell lines in vitro . Multiple array-based drug screens have been performed in HNSCC cell lines and primary HNSCC cells in 2D tissue culture, to identify synergistic drug combinations or new targets for therapy [ 139 , 140 , 141 , 142 , 143 , 144 ]. These screens prominently identified many cell cycle and DNA damage response inhibitors impacting survival of HNSCC cells.…”
Section: Identification Of Essential Genes In (Pre)hnscc Cells By Descriptive and Functional Genomicsmentioning
confidence: 99%